A Comparative Study of the Coordination of Cricket and Volleyball Players - Shaileshkumar J. Makvana; Dr. Vishnu Chaudhari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The purpose of this research was to conduct a comparative study of the coordination of movements of cricket and volleyball players. In this research study, 12 cricket and 12 volleyball players were selected as subjects. Thus, a total of 24 subjects were selected. In the measurement standard, the coordination of movements was measured by eye-hand coordination. To compare the coordination of movements of cricket and volleyball players, the ‘t’ test was applied and the significance level was set at 0.05. The conclusion was as follows. There was no significant difference in the coordination test performance of volleyball and cricket players.